Lithium-ion battery anode material and method for making same
A binary binder system with cyclized PAN and PVDF enhances silicon-graphite interaction in Li-ion battery anodes, addressing efficiency and stability issues, thereby improving cycle life and conductivity.
Patent Information
- Application Number
- JP2024535651
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-16
- Filing Date
- 2022-12-16
- Publication Date
- 2024-12-26
AI Technical Summary
Existing Li-ion battery anode materials face challenges in achieving high energy density and stability due to inefficiencies in binding silicon and graphite particles, leading to capacity degradation and limited cycle life.
Employing a binary binder system comprising a first polymeric binder that undergoes cyclization, such as cyclized polyacrylonitrile (PAN), and a second binder like poly(vinylidene fluoride) (PVDF), which interacts differently with silicon and graphite particles to control expansion and enhance conductivity.
The dual binder system improves the cycle life and conductivity of the anode, allowing for better performance and stability in Li-ion batteries.
Smart Images

Figure 2024546892000001_ABST
Abstract
Description
[Technical field]
[0001] cross reference This application claims the benefit of the filing date of U.S. Provisional Patent Application No. 63 / 290,371, filed December 16, 2021, which is incorporated by reference in its entirety herein.
[0002] The present disclosure relates to anode materials for improving conductivity, specific capacity, and cycle life stability, and methods for producing high capacity anode materials suitable for use in electrochemical energy storage devices. More specifically, the present disclosure relates to the use of two or more polymer binders in Li-ion battery anode materials, such as polyacrylonitrile (PAN) and poly(vinylidene fluoride) (PVDF); combinations of PAN, PVDF, and polyimide (PI); and other combinations of polymer binders. [Background technology]
[0003] Lithium-ion (Li-ion) batteries are used in large quantities in consumer electronics, electric vehicles (EVs), energy storage systems (ESSs), and smart grids. The energy density of Li-ion batteries depends, at least in part, on the anode and cathode materials used. Optimization of Li-ion battery processing and manufacturing has enabled a 4-5% improvement in the energy density of Li-ion batteries each year, but these incremental improvements are not sufficient to reach the energy density targets of next generation technologies. Reaching such targets will require advances in electrode materials, such as the incorporation of high energy density active materials within the electrodes. Recent research has focused primarily on the development of high energy cathodes, with only limited work devoted to the development of anode materials.
[0004] Recently, silicon has emerged as one of the most attractive high-energy anode materials for Li-ion batteries. Silicon's low working voltage and high theoretical specific capacity of 3579 mAh / g are nearly 10 times that of traditional graphite, thus bringing more interest. U.S. Patents 10,573,884 and 10,707,481 describe anode compositions that include silicon active material particles and a single polymer binder such as polyacrylonitrile (PAN). The '884 and '481 patents describe PAN as the sole polymer binder present in the anode material, and further describe how the PAN polymer binder can be cyclized.
[0005] The technique of adding graphite to pure silicon-based anodes is commonly used to add a structural matrix around the silicon particles and allow higher conductivity within the anode. In silicon-based anode designs with less than 25 wt% graphite, the PAN binder wraps the silicon particles and allows controlled fragmentation, improving anode conductivity, while the graphite particles act as a structural matrix. In anode designs with higher graphite content (i.e., greater than 25 wt%), the PAN binder does not effectively bind both the silicon and graphite particles, and the unbound graphite particles cause capacity degradation in the cell. Thus, there is a need for improved anode materials for Li-ion batteries. Summary of the Invention
[0006] According to an aspect of the present disclosure, an anode configured for use in an electrochemical energy storage device is provided that includes: a plurality of active material particles; a first cyclized polymer binder; and a second polymer binder, where the first polymer binder is a different type of polymer binder than the first polymer binder.
[0007] According to another aspect of the present disclosure, an electrochemical energy storage device is provided that includes an anode comprising a plurality of active material particles, a first cyclized polymer binder, and a second polymer binder, where the first polymer binder is a different type of polymer binder than the second polymer binder; a cathode; and an electrolyte comprising at least one lithium salt.
[0008] According to another aspect of the present disclosure, there is provided a method of making an anode for use in an electrochemical energy storage device, comprising: a) mixing together a plurality of active material particles, a first polymeric binder that undergoes a cyclization reaction when heated, and a second polymeric binder (of a different type than the first polymeric binder) to form a mixture; b) coating the mixture onto a current collector to form a coated current collector; and c) subjecting the coated current collector to a temperature treatment. A method is provided that includes:
[0009] These and other aspects of the present disclosure will become evident upon consideration of the following detailed description and claims appended hereto. [Brief description of the drawings]
[0010] [Figure 1] 1 is a flow diagram illustrating a method of making an anode material according to various embodiments described herein. [Figure 2A] FIG. 13 is a photograph showing images of an anode electrode prepared with PVDF as a single polymer binder from a full pouch cell, where substantial swelling was observed and the coating delaminated after lithiation was completed. [Figure 2B] 1 is a photograph of the anode electrode after lithiation is complete, showing substantial expansion. [Figure 3A] Photographs showing images of anode coating materials prepared with two different types of polymer binders (i.e., cyclized PAN binder and PVDF binder). [Figure 3B]Photograph showing the linear dimension of the anode coating. [Figure 3C] Photograph showing thickness dimensions of the anode coating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Described herein are various embodiments of Li battery anode materials and methods of making the same, where the anode materials include at least a first polymer binder that undergoes a cyclization reaction when heated, and a second polymer binder.
[0012] In some embodiments, an anode configured for use in an electrochemical energy storage device is described. The anode includes a plurality of active material particles, a first polymer binder, and a second polymer binder. The first polymer binder is a different type of polymer binder than the second polymer binder. One of the two different types of polymer binders must undergo a cyclization reaction when heated. In some embodiments, the first polymer binder is polyacrylonitrile (PAN) (e.g., including cyclized PAN) and the second polymer binder is poly(vinylidene fluoride) (PVDF).
[0013] In some embodiments, an electrochemical energy storage device is described that includes an anode, a cathode, and an electrolyte. The anode includes a plurality of active material particles, a first polymer binder, and a second polymer binder. The first polymer binder is a different type of polymer binder than the second polymer binder. One of the two different types of polymer binders must undergo a cyclization reaction when heated. In some embodiments, the first polymer binder is PAN (e.g., including cyclized PAN) and the second polymer binder is PVDF.
[0014] In some embodiments, a method of making an anode active material is described that includes mixing together a plurality of active material particles, a first polymer binder that undergoes a cyclization reaction when heated, and a second polymer binder to form a mixture; coating the mixture onto a current collector, such as copper, to form a coated current collector; and subjecting the coated current collector to a temperature treatment. In some embodiments, the first polymer binder is PAN (e.g., including cyclized PAN) and the second polymer binder is PVDF.
[0015] Described herein are various embodiments of anode materials that include active material particles (e.g., silicon and graphite particles), a first polymer binder that undergoes a cyclization reaction when heated, and a second polymer binder. The use of two types of binders can help control the expansion of the active silicon particles, allowing sufficient conductivity in the anode, and binding the active graphite particles together. As a result, the use of a dual binder system in the anode material can improve the cycle life of the battery in which the anode material is used.
[0016] The anode material includes at least a first polymer binder that undergoes a cyclization reaction when heated, and a second polymer binder, the first polymer binder being a different type of polymer binder than the second polymer binder. Polymer binders with different functional groups, such as -COOR, -OH, -NH2, -C≡N, and -CF, are defined as different types of binders. The binders can also be differentiated based on their ability to bond with the Si active material. For example, CF bonds are not reactive and therefore will not bond with Si particles, while reactive functional groups will interact with Si particles by forming hydrogen bonds, ion-dipole bonds, and the like. The specific types of polymer binders used in the first and second polymer binders are generally not limited, nor are the specific combinations of polymer binders used in the first and second polymer binders. Exemplary polymer binders that can be used for either the first or second polymer binder include, but are not limited to, polyacrylonitrile (PAN), poly(vinylidene fluoride) (PVDF), polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyimide (PI), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC).
[0017] In some embodiments, the first polymer binder is polyacrylonitrile (PAN). In some embodiments where PAN is used as the first polymer binder component of the anode material, the anode material may be prepared and / or treated in such a manner that the PAN becomes cyclized PAN. That is, in the final form of the anode material, the first polymer binder is cyclized PAN. Any method of preparing and / or treating the anode material to cyclize the PAN may be used. In some embodiments, the anode material is heated within a range of about 200° C. to about 600° C. to cyclize the PAN polymer binder component. In some embodiments, the anode material is heated to a temperature above 230° C. to effect this cyclization. In some embodiments, a temperature range between 240° C. and 400° C. is used.
[0018] In some embodiments where the first polymer binder is PAN, the second polymer binder is PVDF.The combination of PAN and PVDF as polymer binder has been found to be a particularly effective mechanism for controlling the expansion of silicon particles, allowing sufficient conductivity at the anode, and binding graphite particles together.
[0019] The total amount of polymer binder used in the anode material is generally not limited. In some embodiments, the total amount of polymer binder (e.g., the combination of the first polymer binder and the second polymer binder) is in the range of about 5 to about 40% by weight of the anode material. The amount of each of the specific polymer binders is also generally not limited. In some embodiments, the anode material is about 5% to about 30% by weight of the first polymer binder and about 1% to about 20% by weight of the second polymer binder. The amount of the first polymer binder and the second polymer binder in the anode material can also be selected based on the ratio of the first polymer binder to the second polymer binder. The ratio of the first polymer binder to the second polymer binder is also generally not limited. In some embodiments, the ratio of the first polymer binder to the second polymer binder in the anode material is about 1:1 to about 4:1.
[0020] In some embodiments, the anode material may include any number of additional polymer binders beyond the first and second polymer binders. For example, in some embodiments, the anode material includes a third polymer binder. The additional polymer binder can be selected from the same list of polymer binders already provided, provided that the additional polymer binder is a different type of polymer binder than the polymer binders used in the first and second polymer binders.
[0021] The anode material described herein further comprises a plurality of active material particles. While any suitable active material particles can be used, in some embodiments, the active material particles comprise silicon particles and graphite particles. Any type of active material particles comprising silicon can be used for the silicon particle component, such as bare silicon particles, Si composite particles, or any combination thereof. In some embodiments, at least some, if not all, of the silicon particles provided in the anode material are Si composite particles. When all silicon particles present in the anode are Si composite particles, the Si composite particles may all be of the same type (e.g., all Si composite particles are Si-carbon particles), or the Si composite particles may be composed of two or more different types of Si composite particles (e.g., some Si composite particles are Si-carbon particles, while other Si composite particles are silicon oxide particles). In embodiments in which the silicon particles comprise both Si composite particles and non-Si composite particles, the Si composite particles may be all one type, or may be one or more types of Si composite particles. The non-Si composite particles may be any suitable type of active material or materials that are not Si composite materials. In some embodiments, the non-Si composite particles included in the anode material are bare silicon particles.
[0022] Any suitable Si composite material can be used for the Si composite particles included in the anode materials described herein. In some embodiments, the Si composite particles are Si-carbon composite materials, such as carbon-coated Si particles. In some embodiments, silicon oxide (SiO x) is used. The Si composite may be an alloy of Si with an inert metal or nonmetal, such as a silicon metal alloy. Other examples of Si composite materials that may be used in the embodiments described herein include graphene-silicon composites, graphene oxide-silicon-carbon nanotubes, silicon-polypyrrole, and composites of nano- and micron-sized silicon particles. As previously described, any combination of Si composite materials may be used in the anode material, or only a single Si composite material may be used.
[0023] In some embodiments, the total active material particle content of the anode material (i.e., the combination of silicon particles and graphite particles) is generally about 30% to about 90% by weight of the anode material, such as about 50% to about 80% by weight. The silicon particles may be about 30% to about 80% by weight of the anode material, and the graphite particles may be about 10% to about 60% by weight of the anode material. In some embodiments, all of the active material particles present in the anode material may have a size ranging from about 1 nm to about 100 μm.
[0024] In embodiments where the first binder is PAN and the second binder is PVDF, the weak van der Waals forces between the PVDF and the graphite particles can be dissociated and highly reversible, whereas hydrogen bonding and ionic dipolar type interactions with the reactive functional groups present in the PAN are required to improve the performance of the silicon-based anode. Thus, the amount of the first polymer and the second polymer used in the anode generally depends on the silicon and graphite content of the anode material.
[0025] Additional components that may be included in the anode material include conductive carbon nanoparticles and acid binders. When conductive carbon nanoparticles are included in the anode material, they may be present in a range of about 0.1% to about 5% by weight. Any suitable conductive nanoparticles may be used, including but not limited to VGCF, carbon black, and carbon nanotubes. The addition of such conductive carbon nanoparticles may increase the conductivity of the anode material. Acid binders that may be included in the anode slurry used to make the anode material may include, for example, oxalic acid, citric acid, maleic acid, tartaric acid, and 1,2,3,4-butanetetracarboxylic acid. Acid binders may be used to improve dispersion and adhesion properties. When used in the anode material, acid binders may be present in a range of about 0.01% to about 2% by weight.
[0026] Beyond the active material particles, first and second polymer binders, conductive carbon nanoparticles, and acid binder already described, the anode materials described herein may include any other materials suitable for use in an anode material. Other materials that may be present in the anode material include, but are not limited to, sulfur, hard carbon, graphite, tin, and germanium particles. When present in the anode material, these materials may be present in a range of about 0.1% to about 60% by weight of the anode composite material.
[0027] The anode materials described herein can be incorporated into an electrochemical energy storage device. The electrochemical energy storage device generally includes the anode materials described herein, a cathode, and an electrolyte. In some embodiments, the electrochemical energy storage device is a lithium secondary battery. In some embodiments, the secondary battery is a lithium battery, a lithium ion battery, a lithium-sulfur battery, a lithium-air battery, a sodium ion battery, or a magnesium battery. In some embodiments, the electrochemical energy storage device is an electrochemical cell, such as a capacitor. In some embodiments, the capacitor is an asymmetric capacitor or a supercapacitor. In some embodiments, the electrochemical cell is a primary cell. In some embodiments, the primary cell is a lithium / MnO2 battery or a Li / poly(carbon monofluoride) battery.
[0028] Suitable cathodes for use in electrochemical energy storage devices include lithium metal oxides, spinels, olivine, carbon-coated olivine, LiCoO2, LiNiO2, LiMn 0.5 Ni 0.5 O2, LiMn 0.3 Co 0.3 Ni 0.3 O2, LiMn2O4, LiFeO2, LiNi x Co y Met z O2, A n’ B2(XO4)3, vanadium oxide, lithium peroxide, sulfur, polysulfides, lithium carbon monofluoride (LiCF x and mixtures of any two or more thereof, where Met is Al, Mg, Ti, B, Ga, Si, Mn, or Co; A is Li, Ag, Cu, Na, Mn, Fe, Co, Ni, Cu, or Zn; B is Ti, V, Cr, Fe, or Zr; X is P, S, Si, W, or Mo; where 0≦x≦0.3, 0≦y≦0.5, and 0≦z≦0.5, and 0≦n 1 According to some embodiments, the spinel has the formula Li 1+xMn 2-z Met''' y O 4-m X' n where Met''' is Al, Mg, Ti, B, Ga, Si, Ni, or Co; X' is S or F; and where 0≦x≦0.3, 0≦y≦0.5, 0≦z≦0.5, 0≦m≦0.5, and 0≦n≦0.5. In other embodiments, the olivine is a spinel manganese oxide of the formula LiFePO4 or Li 1+x Fe 1z Met” y PO 4-m X' n where Met″ is Al, Mg, Ti, B, Ga, Si, Ni, Mn, or Co; X′ is S or F; and where 0≦x≦0.3, 0 0≦y≦0.5, 0≦z≦0.5, 0≦m≦0.5, and 0≦n≦0.5.
[0029] In some embodiments, the electrolyte component of an electrochemical energy storage device includes an aprotic organic solvent system, a metal salt, and at least one additive.
[0030] In some embodiments, the aprotic organic solvent based component of the electrolyte is selected from open chain or cyclized carbonates, carboxylate esters, nitriles, ethers, sulfones, sulfoxides, ketones, lactones, dioxolanes, glymes, crown ethers, siloxanes, phosphate esters, phosphines, mono- or polyphosphazenes, or mixtures thereof in the range of 20% to 90% by weight.
[0031] In some embodiments, the metal salt component of the electrolyte is in the range of 10% to 30% by weight of lithium salts, such as Li(AsF6);Li(PF6);Li(CF3CO2);Li(C2F5CO2);Li(CF3SO3);Li[N(CP3SO2)2];Li[C(CF3SO2)3];Li[N(SO2C2F5)2];Li(ClO4);Li(BF4);Li(PO2F2);Li[PF2(C2O4)2];Li[PF4C2O4];Lithium alkyl fluorophosphates;Li[B(C2O4)2];Li[BF2C2O4];Li2[B 12 Z 12-j H j ];Li2[B 10 X 10-j’ H j’ or a mixture of any two or more of these, where Z is independently at each occurrence a halogen, j is an integer from 0 to 12, and J′ is an integer from 1 to 10.
[0032] In some embodiments, the at least one additive is a compound containing at least one unsaturated carbon-carbon bond, a carboxylic acid anhydride, a sulfur-containing compound, a phosphorus-containing compound, a boron-containing compound, a silicon-containing compound, or a mixture thereof, in the range of 0.1% to 10% by weight.
[0033] In some embodiments where the electrochemical energy storage device is a secondary battery, the secondary battery may further include a separator separating the positive and negative electrodes. The separator for lithium batteries is often a microporous polymer film. Examples of polymers for forming the film include polypropylene, polyethylene, nylon, cellulose, nitrocellulose, polysulfone, polyacrylonitrile, polyvinylidene fluoride, polybutene, or a copolymer or blend of two or more such polymers. In some cases, the separator is a microporous polyolefin separator that has been treated with an electron beam. The electron treatment can increase the deformation temperature of the separator, thus increasing its thermal stability at high temperatures. Additionally or alternatively, the separator can be a shutoff separator. The shutoff separator may have a trigger temperature greater than about 130° C. to allow the electrochemical cell to operate at temperatures up to about 130° C.
[0034] Referring to FIG. 1 , a flow diagram illustrating an embodiment of a method 100 for preparing an anode material described herein includes step 110 of mixing active material particles, a first polymer binder that undergoes a cyclization reaction when heated, and a second polymer binder together to form a mixture, step 120 of adding a solvent to the mixture and coating the mixture onto a copper current collector, and step 130 of removing the solvent from the coating and subjecting the coated current collector to a heat treatment.
[0035] According to step 110, the active material particles, the first polymer binder, and the second polymer binder are mixed together to form a mixture. While any technique for mixing these materials together can be used, in some embodiments, mechanical mixing is used. For example, the components can be mixed together by ball milling the solids at low rpm. Typically, the polymer binder is mixed with a solvent, and then the solids are added to the slurry and dispersed using high shear mixing.
[0036] In step 120, a solvent is added to the mixture to disperse the active material particles. Any suitable solvent can be used in any suitable amount. In some embodiments, the solvent is anhydrous NMP. Other suitable solvents include, but are not limited to, N,N-dimethylformamide (DMF), dimethylsulfone (DMSO2), dimethylsulfoxide (DMSO), ethylene carbonate (EC), and propylene carbonate (PC). The solvent can be mixed with the mixture of silicon composite particles and polymer binder for any suitable length of time, for example, about 12 hours. Solvent mixing can be performed using high shear centrifugal mixing or using a stir bar in a glass vial.
[0037] Step 120 further includes coating the slurry mixture onto a current collector. The material of the current collector can be any suitable current collector material, such as copper. The coating step can be performed using any suitable technique and equipment, for example, a benchtop doctor blade coater.
[0038] In step 130, the solvent is removed from the material coated on the current collector and then the coated current collector is subjected to a heat treatment. Although this step is described as two separate operations, in some embodiments it may be possible to remove the solvent from the coating as part of the heat treatment step. When the solvent is first removed, it may be removed by heating the coating at a temperature that is generally lower than the temperature used in the subsequent heat treatment step, but higher than the temperature required to remove the solvent from the coating. For example, in some embodiments, the solvent is removed from the coating by first subjecting the coated current collector to a temperature of about 60° C. (such as in a convection oven) to evaporate the solvent.
[0039] After solvent removal, step 130 continues with subjecting the coated current collector to a heat treatment. The heat treatment may include heating the coated current collector in an inert atmosphere to a temperature ranging from about 200° C. to about 600° C., for example, in an inert argon gas atmosphere at about 330° C. The temperature may range from about 240° C. to about 400° C. In embodiments where the first or second polymer binder is PAN, the heat treatment step may be aimed at cyclizing the PAN component. Cyclization of PAN is a process when nitrile bonds (C≡N) are converted to double bonds (C═N) due to crosslinking of PAN molecules. This process results in ladder polymer chains of PAN fibers that are elastic but mechanically robust, thus allowing for controlled fragmentation of the silicon particles.
[0040] From the foregoing, it will be understood that, although specific embodiments of the present invention have been described herein for purposes of illustration, various modifications may be made without departing from the scope of the disclosure. The disclosure is further illustrated with reference to the following specific examples. It will be understood that these examples are provided by way of illustration and are not meant to limit the scope of the disclosure or the claims which follow. EXAMPLES
[0041] Example 1 The silicon composite material was mixed with 150,000 MW (150K) PAN and PVDF polymer binder by ball milling the solids at low rpm. Conductive carbon additive C65 was dispersed using centrifugal mixing using anhydrous NMP as the solvent, and then the silicon / PAN solids mixture was added to the dispersion. The slurry was mixed overnight and slurried onto a copper current collector using a benchtop doctor blade coater to obtain a coating density of >3 mg / cm. 2Electrodes with solid loading were obtained. The electrodes were dried at 60°C to remove the NMP solvent. All other electrodes containing PAN binder, except for the comparative electrode containing a single PVDF binder shown in Figure 2, were then heat treated at 330°C in an inert argon atmosphere. During the heat treatment process, the PAN binder undergoes a cyclization process to convert the suspended nitriles (triple bonds) to conjugated nitrile groups. To demonstrate the effectiveness of the cyclized PAN binder in providing both mechanical integrity and conductivity, a full pouch cell was prepared by thermally insulating the pouch cell with an NMC811 cathode (4 mAh / cm 2 ) Table 1 compares the full cell data for the anode compositions shown in Table 1. The combination of two polymer binders (PAN and PVDF) provides better performance compared to anodes containing either PAN or PVDF as the only single binder.
[0042] [Table 1]
[0043] Example 2 The silicon composite material was mixed with 150,000 MW (150K) PAN polymer binder by ball milling the solids at low rpm. Using anhydrous NMP as the solvent, the PVDF was dispersed using centrifugal mixing, and then the silicon / PAN solids mixture was added to the dispersion. The slurry was mixed overnight and slurried onto a copper current collector using a benchtop doctor blade coater to obtain a coating density of >3.5 mg / cm. 2 An electrode with a solid loading was obtained. The electrode was dried at 60° C. to remove the NMP solvent. The electrode was then heat treated at 330° C. in an inert argon atmosphere.
[0044] Thus, through the roll-to-roll anode coating process, we are able to engineer the surface chemistry of silicon materials. The coating driven by the cyclized PAN polymer binder gives silicon its mechanical strength, electrical conductivity, and chemical stability, addressing the main challenges.
[0045] While various embodiments have been shown and described in detail herein, it will be apparent to those skilled in the relevant art that various modifications, additions, substitutions, and the like can be made without departing from the spirit of the disclosure and are therefore deemed to be within the scope of the present disclosure as defined in the claims which follow.
Claims
1. 1. An anode configured for use in an electrochemical energy storage device, comprising: A plurality of active material particles; a first cyclized polymeric binder, and a second polymer binder, the first polymer binder being a different type of polymer binder than the first polymer binder; an anode.
2. 2. The anode of claim 1, wherein the first cyclized polymer binder is cyclized polyacrylonitrile (PAN).
3. 10. The anode of claim 1, wherein the second polymer binder is poly(vinylidene fluoride) (PVDF).
4. 2. The anode of claim 1, wherein the ratio of the first cyclized polymer binder to the second polymer binder in the anode is from about 1:1 to about 4:
1.
5. 10. The anode of claim 1, wherein the anode comprises from about 5% to about 30% by weight of the first cyclized polymer binder and from about 1% to about 20% by weight of the second polymer binder.
6. The anode of claim 1 further comprising a third polymeric binder.
7. The anode of claim 1 , wherein the active material particles comprise silicon particles and graphite particles.
8. The anode of claim 7 , wherein the active silicon particles comprise bare silicon particles.
9. The anode of claim 7 , wherein the silicon particles comprise Si composite particles.
10. The anode of claim 9, wherein the Si composite particles comprise a silicon-carbon composite material, a silicon oxide particle, or a silicon metal alloy.
11. 10. The anode of claim 1, wherein each of the plurality of active material particles has a particle size ranging from about 1 nm to about 100 μm.
12. 10. The anode of claim 1, further comprising conductive carbon nanoparticles present in the anode in the range of about 0.1% to about 5% by weight.
13. 13. The anode of claim 12, wherein the conductive carbon nanoparticles comprise vapor grown carbon fibers (VGCF), carbon black, carbon nanotubes, or a mixture thereof.
14. 10. The anode of claim 1, further comprising an acid binder in the range of about 0.01% to about 2% by weight in the anode.
15. The anode of claim 14, wherein the acid binding agent comprises oxalic acid, citric acid, maleic acid, tartaric acid, 1,2,3,4-butanetetracarboxylic acid, or a mixture thereof.
16. A plurality of active material particles; a first cyclized polymeric binder, and the first polymer binder is a different type of polymer binder than the second polymer binder; an anode comprising: A cathode; an electrolyte comprising at least one lithium salt; 1. An electrochemical energy storage device comprising:
17. The device of claim 16 , wherein the first polymer binder is cyclized polyacrylonitrile (PAN).
18. The device of claim 16 , wherein the second polymer binder is poly(vinylidene fluoride) (PVDF).
19. 17. The device of claim 16, wherein the ratio of first cyclized polymer binder to second polymer binder in the anode is from about 1:1 to about 4:
1.
20. 17. The device of claim 16, wherein the anode comprises from about 5 to about 30% by weight of the first cyclized polymer binder and from about 1 to about 20% by weight of the second polymer binder.
21. The device of claim 16 further comprising a third polymeric binder.
22. The device of claim 16 , wherein the active material particles include silicon particles and graphite particles.
23. 23. The device of claim 22, wherein the silicon particles comprise bare silicon particles.
24. The device of claim 22 , wherein the silicon particles comprise Si composite particles.
25. The device of claim 24, wherein the Si composite particles comprise a silicon-carbon composite material, a silicon oxide particle, or a silicon metal alloy.
26. 20. The device of claim 16, wherein each of the plurality of active material particles has a particle size ranging from about 1 nm to about 100 μm.
27. 17. The device of claim 16, wherein the cathode comprises lithium metal oxide, spinel, olivine, carbon-coated olivine, vanadium oxide, lithium peroxide, sulfur, polysulfides, lithium carbon monofluoride, or mixtures thereof.
28. 17. The device of claim 16, wherein the cathode comprises a transition metal oxide material and a hyperlithiated oxide material.
29. 17. The device of claim 16, further comprising a porous separator separating the anode and the cathode from each other.
30. 1. A method of making an anode for use in an electrochemical energy storage device, comprising: b) mixing together a plurality of active material particles, a first polymeric binder that undergoes a cyclization reaction when heated, and a second polymeric binder to form a mixture; c) coating the mixture onto a current collector to form a coated current collector; and d) subjecting the coated current collector to a temperature treatment. A method comprising:
31. 31. The method of claim 30, wherein subjecting the coated current collector to the temperature treatment comprises heating the coated current collector in an inert atmosphere to a temperature in the range of about 200°C to about 600°C.
32. 31. The method of claim 30, wherein the coated current collector is heated to a temperature in the range of about 240°C to about 400°C.
33. After step a) and before step b), the method further includes adding a solvent to the mixture to disperse the active material particles, the first polymer binder, and the second polymer binder, the solvent being selected from the group consisting of N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), dimethylsulfone (DMSO), and the like. 2 ), dimethylsulfoxide (DMSO), ethylene carbonate (EC), and propylene carbonate (PC).
34. After step b) and before step c), removing the solvent from the mixture coated on the current collector.
34. The method of claim 33, further comprising:
35. 31. The method of claim 30, wherein said step c) removes solvent from the mixture coated on the current collector.
36. 31. The method of claim 30, wherein the active material particles range in size from about 1 nm to about 100 μm.
37. 31. The method of claim 30, wherein the mixture formed in step a) comprises 30% to 90% by weight of active material particles.
38. 31. The method of claim 30, wherein the mixture formed in step a) comprises 5% to 40% by weight of the first polymeric binder and the second polymeric binder.
39. 31. The method of claim 30, wherein the first polymeric binder is polyacrylonitrile (PAN).
40. 31. The method of claim 30, wherein the second polymer binder is poly(vinylidene fluoride) (PVDF).
41. 31. The method of claim 30, wherein the ratio of the first polymeric binder to the second polymeric binder in the mixture is from about 1:1 to about 4:
1.
42. 31. The method of claim 30, wherein the mixture comprises about 5% to about 30% by weight of the first polymeric binder and about 1% to about 20% by weight of the second polymeric binder.
43. 31. The method of claim 30, further comprising adding a third polymeric binder to form the mixture.
44. The method of claim 30 , wherein the active material particles include silicon particles and graphite particles.
45. 45. The method of claim 44, wherein the silicon particles comprise bare silicon particles.
46. 45. The method of claim 44, wherein the silicon particles comprise Si composite particles.
47. 47. The method of claim 46, wherein the Si composite particles comprise silicon-carbon composite material, silicon oxide particles, or silicon metal alloy.
